Pharmacology, Toxicology, and Metabolism of Sennoside A, A Medicinal Plant-Derived Natural Compound - Le, Jiamei; Ji, Houlin; Zhou, Xiaoxiao; Wei, Xindong; Chen, Yifan; Fu, Yi; Ma, Yujie; Han, Qiuqin; Sun, Yongning; Gao, Yueqiu; Wu, Hailong (Frontiers in Pharmacology, 2021)
Sennoside A (SA) is a natural dianthrone glycoside mainly from medicinal plants of Senna and Rhubarb, and used as a folk traditional irritant laxative and slimming health food. Accumulating evidences suggest that SA possesses numerous pharmacological properties, such as laxative, anti-obesity, hypoglycemic, hepatoprotective, anti-fibrotic, anti-inflammatory, anti-tumor, anti-bacterial, anti-fungal, anti-viral, and anti-neurodegenerative activities. These pharmacological effects lay the foundation for its potential application in treating a variety of diseases. However, numerous published studies suggest that a long-term use of SA in large doses may have some adverse effects, including the occurrence of melanosis coli and carcinogenesis of colon cancer, thereby limiting its clinical use. It remains to be established whether SA or its metabolites are responsible for the pharmacological and toxicity effects. In this review, the latest advances in the pharmacology, toxicology, and metabolism of SA were summarized based on its biological characteristics and mechanism.